Identify the Rhodamin B on lipsticks in the market Using Thin Layer Chromatography (TLC) Method - Nurul Fajriani; Hadi Kurniawan; Fajar Nugraha (State University of Gorontalo, 2022)
Rhodamine B is a synthetic dye used as a dye for paper and textiles. This dyeis prohibited from being used in cosmetics including lipstick because it can cause skin irritation, irritation to the digestive tract, poisoning, and can cause cancer. The research aims to identify Rhodamine B contained in lipstick circulating in the market area of Pontianak City. Sampling was carried out using purposive sampling technique, obtained 7 samples of lipstick circulating in the market area of Pontianak City. The analysis of Rhodamine B in this lipstick was carried out by Thin Layer Chromatography method using silica gel plate GF 254 and the mobile phase is a mixture of n-butanol, ethyl acetate, and ammonia in a ratio (10:4:5). The results of this study obtained 2 positive samples containing Rhodamine B, namely samples A and E. The Rf values in the samples were 0.75 and 0.675, which were close to the Rf value for the comparison of Rhodamine B, which was 0.7375. The identification results showed that from 7 lipstick samples there were 2 samples positive for Rhodamine B dye.